Hyperlocal Media: Promoting Local Culture - Jati, Rocky Prasetyo (RSF Conference Series: Business, Management and Social Sciences, 2021)
As shown by the world's technology innovation, the development of the digital era makes information dissemination more dynamic. Rapid progress is taking place worldwide, with outstanding digital media capabilities that may help any community. People may easily convey their wants, which can then be funneled through digital media's various services provided and managed. Nowadays, anyone may create media by using some platforms. Everyone may easily manage their website, such as a blog, communicate their goals via a Facebook page, or submit images or videos to illustrate their goals using YouTube or the Instagram application. The local cultural community in Central Java has one fundamental goal: to conserve local art and culture, which is further enhanced by the development of technology-based community media. This is a noble objective. The global community will be aware of, grasp, participate in, or pay attention to the culture that has emerged due to this civilization's history and beginnings. In today's digital context, local cultural communities develop community media that blends online and offline activity. Mergers occur for creative expression and cultural community appreciation, and they influence communication among community media creators. Based on earlier research, this study will discuss the techniques employed by local cultural groups to preserve community media, utilizing the term hyperlocal media and motivated by the notion of cooperative communication. This article wants to show how the Komunitas Bali Buja, as a cultural community, seeks to maintain local wisdom values contained in artistic expression through online-based community media. Community media managers use advanced media technology options for hyperlocal media implementation.